MOTIVATION OF CONVENTIONAL CIGARETTE AND ELECTRIC CIGARETTE USERS IN SOCIOLOGY STUDENTS OF UNM - Riri Amandaria .,; Mauliadi Ramli . (Program Studi Sosiologi, 2022)
AbstractCigarettes are rolled tobacco rolled or wrapped in paper, leaves or corn husks, the size of a little finger with a length of 8-10 cm, usually smoked by someone after burning the tip. In Indonesia, a new trend is now emerging, namely the use of electric cigarettes or vaporizers. Vaporizer is a simple tool that can deliver nicotine through a battery working system into the human body. Nicotine in various doses is inhaled by the user through a tube. Most vaporizers consist of some contents: a rechargeable lithium battery, an atomizer (which heats the liquid to create vapor), and a tube. The standard liquid product contains nicotine, propylene glycol, flavors, and water. This study aims to determine the motivation behind the use of conventional cigarettes and e-cigarettes among Sociology students at UNM, and to determine the social and health impacts felt by users of conventional cigarettes and e-cigarettes for UNM Sociology students. The type of research used in this research is qualitative with a descriptive approach, and the data collection techniques used are observation, interviews, and documentation. Keywords: conventional cigarette, electric cigarette, social motivationAbstractCigarettes are rolled tobacco rolled or wrapped in paper, leaves or corn husks, the size of a little finger with a length of 8-10 cm, usually smoked by someone after burning the tip. In Indonesia, a new trend is now emerging, namely the use of electric cigarettes or vaporizers. Vaporizer is a simple tool that can deliver nicotine through a battery working system into the human body. Nicotine in various doses is inhaled by the user through a tube. Most vaporizers consist of some contents: a rechargeable lithium battery, an atomizer (which heats the liquid to create vapor), and a tube. The standard liquid product contains nicotine, propylene glycol, flavors, and water. This study aims to determine the motivation behind the use of conventional cigarettes and e-cigarettes among Sociology students at UNM, and to determine the social and health impacts felt by users of conventional cigarettes and e-cigarettes for UNM Sociology students. The type of research used in this research is qualitative with a descriptive approach, and the data collection techniques used are observation, interviews, and documentation. Keywords: conventional cigarette, electric cigarette, social motivation